2020
DOI: 10.13057/biodiv/d211045
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of tidal swamp rice from South Kalimantan, Indonesia based on the agro-morphological markers

Abstract: Abstract. Mursyidin DH, Khairullah I. 2020. Genetic evaluation of tidal swamp rice from South Kalimantan, Indonesia based on the agro-morphological markers. Biodiversitas 21: 4795-4803. A total of 71 cultivars of the tidal swamp rice (Oryza sativa L.), originated mainly from South Kalimantan, Indonesia, were evaluated agro-morphologically by using 26 qualitative and 13 quantitative traits. Based on these traits, this germplasm is generally low in diversity. However, three agro-morphological traits, namely the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
(30 reference statements)
2
11
0
Order By: Relevance
“…In this study, Indonesian swamp rice had low genetic diversity, for both qualitative (Table 1) and quantitative (Table 2) characters. This was consistent with Mursyidin and Khairullah (2020), particularly regarding the tidal swamp rice of South Kalimantan Indonesia. Compared to several other studies, such as Suriyagoda et al (2011); Rabara et al (2014) and Sinha et al (2015), this germplasm showed lower diversity.…”
Section: Importance Of Genetic Diversity and Its Related Factorssupporting
confidence: 86%
See 4 more Smart Citations
“…In this study, Indonesian swamp rice had low genetic diversity, for both qualitative (Table 1) and quantitative (Table 2) characters. This was consistent with Mursyidin and Khairullah (2020), particularly regarding the tidal swamp rice of South Kalimantan Indonesia. Compared to several other studies, such as Suriyagoda et al (2011); Rabara et al (2014) and Sinha et al (2015), this germplasm showed lower diversity.…”
Section: Importance Of Genetic Diversity and Its Related Factorssupporting
confidence: 86%
“…Each value of H was standardized by conversion to a relative phenotypic diversity index (H′) by division by H max = ln(n) to express the H′ value in the range of 0-1. The level of this diversity was categorized as high (H′ > 0.60), moderate (0.40 ≤ H′ ≤ 0.60) or low (H′ < 0.40) (Mursyidin and Khairullah, 2020). Pearson correlations (r) among agro-morphological characters were analyzed using the Excel ver.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations